Some productivity characteristics of chukar partridges (a. chukar) in different - Orhan Çetin; Kemal Kırıkçı; Nurettin Gülşen (Eurasian Journal of Veterinary Sciences)
This study has been carried out tor determining egg production, hatchability and growing characteristics in intensive conditions of the Chukar partridges which are local wild species in Türkiye. Adult Chukar partridges from different regions of Anatolia were divided into two groups. In first group, there were 5 male and S female aduft Chukar partridges and they were mated one by one in cages. In second group, there were 5 male and 5 female adult Chukar partridges and they were mated in flock. Average number of egg production, egg production percentage, egg weight, fertility, hatchability, and hatchability of fertilized eggs of flock and cage Chukar partridges groups were determined as: 38.40 and 11.20, 47% and 16 %, 19 31 g and 18.99 g. 89 06 % and 57.14%, 81.25 % and 53.57 % and 91.11 % and 93.75 % respectively. There were statistically significant differences between groups in respects of egg weight and egg production percentage (P<0.01); egg production, fertility and hatchability (P<0.001). But there were no sta tistically significant differences between groups in respects of hatchability ot fertilized eggs {P>0.05). Egg production period of flock and cages Chukar partridges were determined as 83 and 68 days respectively. Average body weights of adult Chukar partridges were determined as 411.39 g, while average body weights of 18 weeks old of Partridge chicks were found as 431.32 g. Date of first oviposition was realized 34 weeks old. As a result of this study Its considered thai for the conservation and supporting of hunting industry of Türkiye, the researches on management and improvement of egg production characteristics must be carried out in Chukar partridges.